Antihypertensive Prescribing Practices: Impact of the Antihypertensive and Lipid‐Lowering Treatment to Prevent Heart Attack Trial - Player, Marty S. (J Clin Hypertens (Greenwich), 2007)
This national study examines the impact of the Antihypertensive and Lipid‐Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) on the prescribing of thiazide‐type diuretics and other antihypertensive medications for patients with newly diagnosed hypertension. A cross‐sectional analysis was conducted using data from a national network of electronic health records for 2 groups with newly diagnosed hypertension and started on antihypertensive medications: one a year before and the other a year after the publication of ALLHAT. The percentage of new hypertensives started on thiazides increased from 29% pre‐ALLHAT to 39% post‐ALLHAT. An increase was also seen for angiotensin receptor blockers, while prescribing for angiotensin‐converting enzyme inhibitors, calcium channel blockers, and β‐blockers declined. There was no significant change in prescriptions for α‐blockers. Prescriptions for thiazides for patients with newly diagnosed hypertension increased after the publication of ALLHAT. Data from large national trials can have a considerable impact on prescribing practices.